Enhanced mechanical properties of double-walled carbon nanotubes reinforced silica aerogels: An all-atom simulation study. (15th April 2021) - Patil, Sandeep P.
Graphical abstract: Abstract: To enhance the mechanical properties of highly porous low strength and stiffness silica aerogel, we proposed double-walled carbon nanotubes (DWCNTs) of different length to diameter ratios as reinforcement material for the silica aerogel matrix using molecular dynamics (MD) simulations. It is found that a small amount of DWCNTs (2.06%) in the silica aerogel resulted in a significant improvement in the tensile strength and elastic modulus, which is mainly due to random distribution of strong and stiff DWCNT fibers. Moreover, the elastic modulus values of nanocomposites increase quadratically with respect to the weight percentage (wt %) of DWCNT fibers. Furthermore, in compression simulations, as the wt % of DWCNT fibers increases, the initial stiffness also increases, and early densification occurs. The presented work helps to design a new composite material for a specific application.